Epidemiological features of meningiomas: a single Brazilian center’s experience with 993 cases - Colli, Benedicto Oscar; Machado, Hélio Rubens; Carlotti, Carlos Gilberto, Jr; Assirati, João Alberto, Jr; Oliveira, Ricardo Santos De; Gondim, Guilherme Gozzoli Podolsky; Santos, Antonio Carlos Dos; Neder, Luciano (Arquivos de Neuro-Psiquiatria, 2021)
Background: Meningiomas are the most frequent primary central nervous system (CNS) tumors. Their geographical and ethnic characteristics need to be known, in order to enable rational treatment. Objective: To investigate clinical and epidemiological aspects in a series of patients with meningiomas. Methods: Retrospective analysis on the demographic profile, location and histopathology of 993 patients with meningiomas (768 operated and 225 not operated). Results: Meningiomas represented 43.8% of the primary CNS tumors; 6.8% were multiple tumors (14.7% with neurofibromatosis 2) and 0.6% were radiation-induced tumors. The mean ages were 53.0 and 63.9 years for operated and non-operated patients and the female/male ratios were 3.2:1 and 6.3:1. Diagnosis was made later among females. The peak incidences were in the 6th and 7th decades respectively for operated and non-operated patients. The incidence was low at early ages and higher among patients aged 70+ years. The meningiomas were intracranial in 96.5% and most were WHO grade I (88.9%) and transitional. In the spinal canal (3.5%), they occurred mainly in the dorsal region (all grade I; mostly transitional). The racial distribution was 1.0% in Asian-Brazilians, 87% in Caucasians and 12% in African-Brazilians. 83.4% and 51.6% of the patients were estimated to be recurrence-free at 10 and 20 years, and the mortality rate was 3%. Conclusions: Most of the demographic data were similar to what has been observed in other western centers. Differences were higher incidence of meningiomas, female and older predominance in non-operated patients, predominance in Caucasian, and higher association with neurofibromatosis 2.
Keywords: Meningioma; Demographic Data; Pathology; General Surgery; Risk Factors; Neoplasm Recurrence, Local